THE EFFECTIVENESS OF ENGLISH SONG LYRICS IN TEACHING READING : A study on the eleventh grade students of Madrasah Aliyah Putra Al-Islahuddiny Kediri - Muhamad Sarifuddin (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2024)
This research is focused In learning Language of English for eleventh grade students of Madrasah Aliyah Putra Al-Islahuddiny Kediri. This research deeply concerned with the use of English song lyrics in teaching reading. In collecting the data, the researcher used reading test. From the test, the researcher got 3 learners can be classified very good, 19 learners have good classification, 4l learners have sufficient classification, 4 learners are bad.Based on score test collected, there was indication that achievement in learning Reading Comprehension with English song lyrics, the eleventh grade students of Madrasah Aliyah Putra Al-Islahuddiny Kediri can indicate very great details for the result of the test taken by the learners. Therefore, it can be seen that the use of English song lyrics in learning Reading Comprehension can influence the teacher’s success in increasing his learners’ learning achievement.